Henckelia inaequalifolia (Gesneriaceae), a new species from Sichuan, China - Shi, Xi-Zuo; Wang, Jia-Cai; Yang, Li-Hua (Phytotaxa, 2021)
Henckelia inaequalifolia, a new species in the genus Henckelia of the family Gesneriaceae is described here. The detailed morphological description, photographic illustration and geographical distribution of the new species are provided. Its morphological affinities between related species are also discussed in this paper.